Plasma proprotein‐convertase‐subtilisin/kexin type 9 (PCSK9) and cardiovascular events in type 2 diabetes. Issue 4 (14th January 2018) - El Khoury, Petra; Roussel, Ronan; Fumeron, Frederic; Abou‐Khalil, Yara; Velho, Gilberto; Mohammedi, Kamel; Jacob, Marie‐Paule; Steg, Philippe Gabriel; Potier, Louis; Ghaleb, Youmna; Elbitar, Sandy; Ragot, Stephanie; et al.
Abstract : Aim: To investigate whether plasma concentrations of proprotein‐convertase‐subtilisin/kexin type 9 (PCSK9) were associated with cardiovascular (CV) events in two cohorts of patients with type 2 diabetes mellitus. Methods: We considered patients from the DIABHYCAR ( n = 3137) and the SURDIAGENE ( n = 1468) studies. Baseline plasma PCSK9 concentration was measured using an immunofluorescence assay. In post hoc, but preplanned, analyses we assessed the relationship between PCSK9 and the following endpoints: (1) a combined endpoint of major CV events: CV death, non‐fatal myocardial infarction (MI), stroke and heart failure‐related hospital admission; (2) a composite of all CV events: MI, stroke, heart failure‐related hospital admission, coronary/peripheral angioplasty or bypass, CV death; (3) MI; (4) stroke/transient ischaemic attack (TIA); and (5) CV death. Results: In the DIABHYCAR study, plasma PCSK9 tertiles were associated with the incidence of MI, all CV events and stroke/TIA ( P for trend <.05). In adjusted Cox analysis, plasma PCSK9 was associated, independently of classic risk factors, with the incidence of major CV events (hazard ratio [HR] for 1‐unit increase of log[PCSK9] 1.28 [95% confidence interval CI 1.06‐1.55]), the incidence of MI (HR 1.66 [95% CI 1.05‐2.63]), and the incidence of all CV events (HR 1.22 [95% CI 1.04‐1.44]), but not with CV death. Plasma PCSK9 was not associated with the incidence of CV disease in the participants of the SURDIAGENE study with high CV risk treated with statins and insulin. Conclusions: We found that PCSK9 was inconsistently associated with CV events in populations with type 2 diabetes. The association may depend on the level of CV risk and the background treatment.